Modeling of Head Linear Accelerator (LINAC) for Study of Photon Beam Characteristics Based on GEANT4 - Nurul Qomariyah; Freddy Haryanto; A Waris; R Subroto; I WA Makmur; Rahadi Wirawan (Indonesian Association of Physicists in Medicine (AIPM/AFISMI), 2023)
A linear accelerator (LINAC) is an external radiotherapy device commonly used to treat cancer. This study aims to model the LINAC head to determine the characteristics of the photon beam generated by LINAC using a GEANT4-based Monte Carlo simulation program approach. The initial stage of the research is to build a LINAC head model. The LINAC head geometry consists of: electron source, tungsten target, flattening filter, primary collimator, X-jaw and Z-jaw, and multi-leaf collimator (MLC). The second stage is simulation data acquisition (running-beam on). In the simulation, physical interactions are in the form of empenelope, electron source particles with a pencil beam model, 0.01mm set cuts, beam on 5 x 107 history, particle energy with variations of 6 MV, 9 MV, and 12 MV, and the measuring area in a water phantom 40cm × 40cm × 40cm. This study uses a source skin distance (SSD) of 100 cm, and a radiation field area of 10cm × 10cm. The simulation results obtained a histogram of the energy spectrum distribution, percent depth dose (PDD), and beam profile (BP). The simulation results show that the energy spectrum of the third variation has the same pattern with peak energies of 0.3646 MV, 0.3837 MV, and 0.3976 MV, respectively, and the average energy of the photon beam is 0.7196 MV, 0.7745 MV, and 0.7763 MV. The value of PDD and BP gets higher along with the energy source. The simulation results show that the model can explain the differences in the photon characteristics of each energy variation.